2019
DOI: 10.1038/s41584-018-0147-9
|View full text |Cite
|
Sign up to set email alerts
|

Pathophysiology, assessment and treatment of psoriatic dactylitis

Abstract: Dactylitis is diffuse swelling of the digits that is usually related to an underlying inflammatory or infiltrative disorder. Psoriatic arthritis (PsA) is the most common severe disease thought to cause dactylitis. Our understanding of the pathogenesis of PsA-related dactylitis comes from experimental animal models of PsA-like disease, as well as advances in imaging and other clinical studies. Clinical trials in PsA have increasingly included dactylitis as an important secondary outcome measure. These studies i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
56
0
12

Year Published

2019
2019
2024
2024

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 53 publications
(72 citation statements)
references
References 81 publications
4
56
0
12
Order By: Relevance
“…This detection supports the cardinal role of enthesitis observed in experimental models of PsA and in also some imaging studies 13 19. Moreover, previous observations showed that accessory pulley as mini-entheses may provide a mechanistic link between enthesitis and tenosynovitis but further work is needed 20 21. In this study, it is interesting to note that psoriatic nail involvement correlated with subclinical inflammation, but only in the arthralgia cohort.…”
Section: Discussionsupporting
confidence: 86%
“…This detection supports the cardinal role of enthesitis observed in experimental models of PsA and in also some imaging studies 13 19. Moreover, previous observations showed that accessory pulley as mini-entheses may provide a mechanistic link between enthesitis and tenosynovitis but further work is needed 20 21. In this study, it is interesting to note that psoriatic nail involvement correlated with subclinical inflammation, but only in the arthralgia cohort.…”
Section: Discussionsupporting
confidence: 86%
“…Such heterogeneity poses challenges in management, particularly in deriving a sufficient evidence base to address clinical subtypes. Dactylitis is a hallmark of PsA1 for which therapeutic strategies remain empirical 2. Commonly, non-steroidal anti-inflammatory drugs (NSAIDs) and local corticosteroid injections are employed 3.…”
Section: Introductionmentioning
confidence: 99%
“…Dactylitis has variable associations to inflammatory lesions, including flexor tenosynovitis (FT), soft tissue oedema (STO), and joint synovitis [ 10 ]. However, these pathophysiological features of dactylitis can only be appreciated with advanced imaging with musculoskeletal-ultrasound (Msk-US) and magnetic resonance imaging (MRI) studies [ 11 , 12 , 13 , 14 ].…”
Section: Introductionmentioning
confidence: 99%